Applications of CRISPR-Cas9 for advancing precision medicine in oncology: from target discovery to disease modeling - Ravichandran, Mirunalini; Maddalo, Danilo (Frontiers in Genetics, 2023)
The CRISPR/Cas9 system is a powerful tool that enables precise and efficient gene manipulation. In a relatively short time, CRISPR has risen to become the preferred gene-editing system due to its high efficiency, simplicity, and programmability at low costs. Furthermore, in the recent years, the CRISPR toolkit has been rapidly expanding, and the emerging advancements have shown tremendous potential in uncovering molecular mechanisms and new therapeutic strategies for human disease. In this review, we provide our perspectives on the recent advancements in CRISPR technology, their use as a tool to refine and its impact on precision medicine, ranging from target identification, disease modeling and, and diagnostics. We also discuss how novel approaches such as epigenome, base as well as prime editing are impacting the preclinical cancer drug discovery space.